Deep sclerectomy with goniosynechiolysis ab interno for chronic glaucoma associated with peripheral anterior synechiae - Mirshahi, Alireza; Raak, Peter; Ponto, Katharina; Stoffelns, Bernhard; Lorenz, Katrin; Scharioth, Gábor B. (Journal of ophthalmology, 2015)
Purpose. To report one-year results of phacoemulsification combined with deep sclerectomy and goniosynechiolysis ab interno for chronic glaucoma associated with peripheral anterior synechiae (PAS). Methods. We retrospectively analyzed medical charts of 16 patients (20 eyes) treated by one-site combined phacoemulsification and deep sclerectomy with goniosynechiolysis ab interno. PAS were transected by a spatula introduced into the anterior chamber through a paracentesis. To account for the correlation of right and left eyes a linear mixed model with unstructured covariance structure was calculated. Results. The mean preoperative intraocular pressure (IOP) was mmHg with medications. One year postoperatively, the mean IOP was mmHg (, paired -test) with medications. A postoperative IOP of ≤21 mmHg without medication was achieved in 17 of 19 eyes (89.5%) and in 12/19 eyes (63.2%) at 3 and 12 months after surgery, respectively. In the remaining eyes (10.5% at 3 months and 36.8% at 12 months), additional medication led to an IOP ≤21 mmHg or the target pressure. No case required further glaucoma surgery. In one eye, conversion of the surgery to trabeculectomy was necessary due to Descemet’s window rupture. Conclusions. With goniosynechiolysis ab interno, effective and safe nonpenetrating glaucoma surgery is possible in presence of PAS.
Gesehen am 26.11.2018